Teknik Penerjemahan Google Translate dan Subtitle YouTube Indonesia Arab; Serial Nussa “Rarra Sakit” - Adelpina, Dea; Prissa, Salma Salsabila; Supriadi, Rinaldi (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research analyzes translation techniques in the official YouTube subtitles for the "Rarra Pain" episode and Google Translate results. With a descriptive qualitative approach, the main data is Indonesian text and Arabic translation from Google Translate and YouTube subtitles. Data collection techniques include documentation, observation, and analysis using content analysis to identify translation techniques. The results of the analysis show that Google Translate uses literal and automatic techniques that are less contextual and sometimes rigid. In contrast, YouTube subtitles exhibit a variety of more adaptive techniques such as literal, modulation, amplification, and reduction. YouTube subtitles more effectively convey messages with appropriate cultural and idiomatic nuances. For series like Nussa, which contain cultural nuances and colloquial language, YouTube subtitles effectively convey the message to Arabic-speaking viewers. This research provides important insights for the development of better translation techniques, especially for children's content.